Forecasting port-level demand for LNG as a ship fuel: The case of the port of Antwerp - Raimonds Aronietis; Christa Sys; Edwin Van Hassel; Thierry Vanelslander (Journal of Shipping and Trade (JST), 2016)
From a European, regional and local perspective, as well as from the point of view of port authorities, it is important that waterborne transport should be sustainable. In this context, liquefied natural gas (LNG) is often put forward as a viable alternative fuel for deep-sea, shortsea and inland navigation. The present paper develops a forecasting method for determining potential LNG bunker volumes at port level. The proposed method is based on a review of the literature, historical data on technological innovation in shipping (i.e. the transitions from sail to steam and marine diesel engines), expert opinions and present-day bunker volumes. The forecast obtained was subsequently validated by shipping companies, bunker companies and fuel suppliers operating in the port of Antwerp. In addition, a sensitivity analysis was conducted to assess the impact of a number of relevant independent variables on the forecast. Overall, it is found that switching to LNG as a ship fuel, like any innovation, exhibits a slow adoption pattern, with sluggish growth initially but picking up some speed with time. At the same time, there is evidence of a chicken-and-egg dilemma, with shipping companies unwilling to invest in LNG-powered ships as long as supply is insufficient or uncertain, and fuel suppliers not willing to provide storage and bunker facilities as long as demand is low. Our analysis points at many uncertainties, which are used as discriminating factors between the different scenarios tested. However, whichever scenario is played out, the indications are that LNG bunkering volumes in Antwerp will not increase sharply between now and 2050. The volume growth under the strong development scenario is about four times greater than that under the weak development scenario, but remains modest.
Keywords: 650; Sustainable shipping; LNG fuel; Forecasting; Port of Antwerp